ICMI : kekuasaan dan demokrasi - Bahar, Ahmad (Yogyakarta : PT. Pena Cendekia Indonesia, 1995)
Views on the All-Indonesia Muslim Intellectuals association ; collection of articles by non-members.
Keywords: ICMI (Organization).; Islam -- Indonesia -- Societies, etc; Intellectuals -- Indonesia -- Societies, etc